Application of the Certainty Factor Method in Expert System for Diagnosing Toddler Diseases - Tou, Nurhaeka; Endraswari, Putri Mentari; Annisa, Nur; Juniawan, Fransiskus Panca (JURNAL SISFOTEK GLOBAL, 2024)
The toddler period is the period after birth up to the age of 59 months. During this period, the immune system in the toddler's body is not yet working optimally, so during this period the toddler is more vulnerable to attacks from various diseases. When a toddler is sick, it is not uncommon for parents to feel confused about what to do or misinterpret the symptoms experienced by the toddler. In conditions like this, the role of a doctor is very necessary. However, in reality, not all parents want to see a doctor, because of the high cost of treatment. Therefore, we need an expert system for diagnosing toddler diseases using the Certainty Factor method to support parents' ease in identifying symptoms and illnesses suffered by toddlers as early as possible. This study used 12 data on toddler illnesses with 51 symptoms. The results of this research show that from the 15 cases that were tested, the precession value was 86.66% and the recall value was 100%. Based on the results of this research, it can be concluded that this system can be used by users to diagnose illnesses in toddlers. With this system, it is hoped that parents can determine the type of disease experienced by toddlers quickly, precisely, and efficiently.